Réponses

2014-03-22T12:37:17+01:00
1) (8x-4)x(2x-3) = A1
(8x-4)x(2+x) = A2
2) (8x-4)+((2x-3)+2+x)
3) après tu remplace x par 6
Meilleure réponse !
2014-03-22T12:50:21+01:00
A = Lxl
a)A₁ = (2x-3)(8x-4)
  A₂ = (x+5)(8x-4)

b) A = A₁ + A₂
   A = (2x-3)(8x-4)+(x+5)(8x-4)
   A = (8x-4)[ (2x-3)+(x+5)]
  A = (8x-4)(3x+2)

c) A₁ = (2*6-3)(8*6-4)          * signifie fois, multiplié par
   A₁ = (12-3)(48-4)
   A₁ = 9*44
   A₁ = 396

  A₂= (6+5)(8*6-4)
  A₂ = 11*44
  A₂ = 484            cela ne colle pas avec l'image

   A = A₁+A₂
   A = 396+484
   A = 880
 Vérif: A = (8*6-4)(3x6+2)
          A = 44*20
          A= 880 OK